Three-dimensional buoyancy-driven convection structures in thermohaline stratification - Ye-Jun Gong; Ying-Ying Luo; Jie-Min Zhan (AIP Advances, 2016)
We report on three-dimensional convection structures in thermohaline stratification with the high Rayleigh number RaT = 7 ⋅ 107, the diffusion ratio δ = 0.01 and various initial density stability ratios R = 0.5, 0.8, and 1.1. According to the classification of buoyancy-driven instability in the parameter space (R, δ), the three cases are referred to follow the Rayleigh-Taylor (RT) mode, the mixed mode (MM) and the diffusive-layer convection (DCL) mode, respectively. Whether the shape of the peak is a finger under the RT mode or a spike under the MM/DLC mode, the 3D view of the interface is likely to be a rolling mountain with a doughnut-shaped vortex around the peak and a banded vortex above the ridge. The doughnut-shaped vortex is maintained around the peak if its growth continues under RT convection; otherwise, the vortex sheds off and moves upward from the peak under the DLC mode. Additionally, we have observed the previously unreported vortex stratification by the contact interface due to the differential diffusion effect.